2021
DOI: 10.3390/polym13142251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composite Core Materials on Fracture Resistance of Endodontically Treated Teeth: A Systematic Review and Meta-Analysis of In Vitro Studies

Abstract: Various material properties are involved in the success of endodontically treated restorations. At present, restorative composites are commonly employed as core build-up materials. This study aimed to systematically review the literature to assess the effect of using composite core materials on the in vitro fracture of endodontically treated teeth. Two different reviewers screened the literature, up to June 2021, in five distinct electronic databases: PubMed (MedLine), Scopus, Scielo, ISI Web of Science, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Risk of bias was determined for each article by three authors, independently. The following parameters were used to determine the risk of bias, according to previous systematic reviews: the presence of a control group; sample size calculation; standardization of the preparation of the samples; sample randomization; sample preparation by a single operator; blindness of the operator; failure mode evaluation [ 18 , 19 ]. For each article, the amount of these parameters that were mentioned in the article was counted.…”
Section: Methodsmentioning
confidence: 99%
“…Risk of bias was determined for each article by three authors, independently. The following parameters were used to determine the risk of bias, according to previous systematic reviews: the presence of a control group; sample size calculation; standardization of the preparation of the samples; sample randomization; sample preparation by a single operator; blindness of the operator; failure mode evaluation [ 18 , 19 ]. For each article, the amount of these parameters that were mentioned in the article was counted.…”
Section: Methodsmentioning
confidence: 99%
“…Two authors (EM, SG) independently assessed the risk of bias of the included studies. This was undertaken according to two previous systemic reviews [24,25]. The following eight parameters were used to evaluate the risk of bias: presence of control group; samples preparation standardization; samples randomization; samples preparation by single operator; materials used according to manufacturer's instruction; blindness of the operator during testing; clarification of calculation of sample size; failure mode evaluation (this one only applied for fracture resistance studies).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Choosing the best material for core build-up in root canaltreated teeth is a hot, yet unsolved topic. In a current systematic review and meta-analysis, Zarow et al concluded that highly filled core composite materials could be a better option compared to classic composite materials [50].…”
mentioning
confidence: 94%